KESINONIMAN NOMINA INSANI DALAM CERITA RAKYAT DAYAK GOLIK KECAMATAN BEDUAI KABUPATEN SANGGAU - Agapitus Susarman; Agus Wartiningsih; Agus Syahrani (Universitas Tanjungpura, 2020)
AbstractThe author examines the To Synonyms in the Dayak Golik Folklore in Sanggau Regency., specifically this research examines the Insani kesinoniman noun consisting of a description of Lexsem subsitution Lexsem. This research aims to (1) Describe the description of lexemes to synonyms noun insani in the folklore of Dayak Golik, (2) describing the subsitution of lexemes to synonyms nouns in Dayak golik folklore, (3) describing the analysis component of the meaning of lexemes to synonyms noun Insani in the Dayak Golik folklore. The data sources in this research are native speakers of Dayak Golik, located in the hamlet of Berinang, Kasromego village, Beduai subdistrict, Sanggau regency. The data collection tool in this research author himself, the author as a key instrument and data collection tool used in this research is a recording tool, a list of questions, and notebooks. Based on data analysis can be concluded first, that the to synonyms noun insani in the story of Dayak people golik there is a noun Insani namely objects such as humans and animals. Secondly, there is Subtusi lexemes that is looking for similarities in Dayak folklore such as Pongan, Banu, investigators who have a meaning in the Indonesian language of pigs. Keywords: Dayak Golik Story, Synonim Insani Noun